Optical manipulation of nematic colloids: Wires, superstructures, and 2D crystals - Muševič, I; Škarabot, M; Ravnik, M; Tkalec, U; Nych, A; Ognysta, U; Nazarenko, V; Žumer, S (2008)
We describe and analyze experiments, where optical manipulation of small colloidal particles in the nematic liquid crystal (NLC) was used to create artificial colloidal structures, such as 1D chains and 2D colloidal crystals, and superstructures of different types of colloids. In all cases, the colloidal particles are strongly bound to each other, with a typical pair interaction energy of several 1000 kBT per 1μm size particle. There are two distinct mechanisms of colloidal binding in a spatially homogeneous NLC: (i) binding via spatially localized topological (point) defects, and (ii) binding via entangled topological defects, where the defect line winds around and wraps several colloidal particles.